Correlation bethealtyy ween dietary glycemic index and glycemic load and blood lipid levels in a group of women from Ahvaz - Farideh Shishebor; Zahra Shamekhi; Majid Karandish; Seyed Mahmood Latifi (Fasa University of Medical Sciences, 2011)
Background & Objectives: There are limited number of studies conducted on the correlation between Glycemic index and Glycemic load of a food program and metabolic factors such as blood lipids in Asian countries including Iran. Therefore, this study aimed at analyzing the correlation between Glycemic index and Glycemic load of Iranian food program and blood lipids. Materials & Methods: The subjects were 95 women working in Ahvaz University of Medical Sciences in the range of 20 to 55 years old. Glycemic index and Glycemic load of the food program was analyzed with 24-hour food recall questionnaires (4-6 recall). For calculating GI and GL, Iranian food GI tables, and also, international GI and GL table were used. The levels of blood lipids including HDL cholesterol, total cholesterol, and triglycerides of the blood were measured and the level of LDL Cholesterol was calculated using Friedewald formula. Also, Anthropometric measurements were done using standard methods. Resulst: The mean age of subjects in this study was 36 years. GI mean was 72.1 and GL mean was 153.2. In this study, there was no significant relation between HDL cholesterol, LDL cholesterol, total cholesterol and Blood TG with Glycemic index and Glycemic load of food program. Conclusion: Unlike findings of west and Asian countries, both dietary GI and GL were not correlated with metabolic factors including blood lipid levels in this study , underreporting of individuals may influence the results of the study.